Heather Raffo's Iraq plays : the things that can't be said : 9 Parts of desire ; Fallujah ; Noura - Raffo, Heather, 1970-; Najjar, Michael Malek, 1972-; Raffo, Heather, 1970- (London ; New York, NY : Methuen Drama/ Bloomsbury Publishing Plc, 2021)
A trilogy of plays by renowned Iraqi American playwright/performer Heather Raffo including '9 Parts of Desire', 'Fallujah', and 'Noura'. In these three works Raffo explores the indelible effects of war on Iraqis, Americans, and the refugees caught between the two cultures. When considered together, these three works give voice to nearly two decades of rarely examined traumas that have reshaped cultural and national identity for both Americans and Iraqis since the events of 9/11.8
Foreword / Joanna Settle -- Acknowledgments -- Introduction / Michael Malek Najjar -- THE PLAYS. 9 parts of desire -- Fallujah -- Noura -- Glossary of Arabic terms and phrases -- Afterword: "The things that can't be said" / Heather Raffo -- Critical essay: "Listening to the soul of rapture - and difference in Heather Raffo's Iraqi-American trilogy" / Maya Roth -- Annotated timeline of the life and works of Heather Raffo -- Bibliography.
Includes bibliographical references (pages 169-172).
Keywords: Iraq -- Drama; Iraq -- Drama